ADF22-WEB: Detection of a Molecular Gas Reservoir in a Massive Quiescent Galaxy Located in a z ≈ 3 Protocluster Core - Hideki Umehata; Mariko Kubo; Kouichiro Nakanishi (The Astrophysical Journal Letters)
We present a study of the molecular gas reservoirs and dust contents in three quiescent galaxies (QGs) located in the core of the z = 3.09 SSA22 protocluster. Using the Atacama Large Millimeter/submillimeter Array, we detect CO(3–2) emission in one galaxy, ADF22-QG1, marking the first direct detection of molecular gas in a QG from the early Universe. The detected galaxy, ADF22-QG1, has a molecular gas mass of log ${M}_{{{\rm{H}}}_{2}}$ / M _⊙  = 10.26 ± 0.07 assuming a CO-to-H2 conversion factor α _CO  = 4.4 (log ${M}_{{{\rm{H}}}_{2}}$ / M _⊙  = 9.52 ± 0.07 for α _CO  = 0.8), corresponding to a gas mass fraction of f _gas  ≈ 14% (2.5%). The gas-to-dust ratio δ _gdr  ≳ 320 ( δ _gdr  ≳ 60) for α _CO  = 4.4 ( α _CO  = 0.8) is also derived for the first time for a QG at the epoch. For the other two galaxies, ADF22-QG2 and ADF22-QG3, nondetections of CO(3–2) emission provide upper limits, f _gas  ≈ 17% (3.1%) and f _gas  ≈ 13% (2.4%), respectively. The inferred gas-consumption history of ADF22-QG1, based on its star formation history, suggests that (i) dusty star-forming galaxies at z = 4–6 are plausible progenitors, and (ii) the cessation of gas accretion from cosmic web filaments plays an important role in their evolution to quenched systems. Furthermore, the presence of a detectable molecular gas reservoir in ADF22-QG1 indicates that additional mechanisms, such as morphological quenching, may be required to fully explain its quiescent nature.